White Todas’. The Politics of Race and Class amongst European Settlers on the Nilgiri Hills c1860 – 1900 - Morrison, Alexander Stephen (My University, 2004)
This article argues that it is not possible to generalise about the politics and racial attitudes of so-called 'unofficial' Europeans in India from observations of the community in Calcutta which, precisely because it was so large, was atypical. Elsewhere where the number of Europeans was smaller, attitudes towards Indians were more complex, and hostility towards the 'official element' of Europeans in civil and military employ with the Government of India was often greater than racial antagonism towards Indians. The Nilgiri Hills in South India, with a population of about 1,500 settlers, are a case in point. The 'White Todas' (the name is taken from a pastoral Hill-tribe) felt distinct from the 'official' Europeans who came up to the main hill-station, Ootacamund, the summer capital of the Madras Presidency, during the hot weather. To avoid complete political emasculation, the 'Todas' at times had to forge political alliances with wealthy Indian mercantile elites, with whom their interests often coincided.
Keywords: British Imperial & Commonwelath History - 19th & 20th century; British Imperial and Colonial History (1600 - ); South Asia (History)